(untitled) (UNWE Yearbook, 2023)
The paper reflects on the rising wave of Neo-Macedonianism in the Republic of North Macedonia (RNM). The author stipulates that this ideology is alive, resilient, and expressed in its most extreme forms. The paper suggests that the political institutions of the EU must be aware of the historical inaccuracies, misleading information, and perpetual violations of the Treaty of friendship, good-neighbourly relations, and cooperation. The author examines the anti-Bulgarian propaganda and all the political, historical, and social complication that such behavior can impose on Bulgarian-Macedonian relations. There is no doubt that the described political phenomena must be taken into consideration, having in mind the possible acceptance of RNM into the European Union.